Analysis of Factors Afeective Employee Performance At BKPSDM Payakumbuh City Using Binary Logistic Regression - Erwan, Erwan; Rica, Rica; Heikal, Jerry (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2024)
This research aimed to examine the factors influencing employee performance at Payakumbuh City Personnel and Human Resources Development Agency (BKPSDM). Using binary logistic regression, the dependent variable (Y) represented employee performance, while the independent variables included work initiative, discipline, qualifications, competence, and leadership. The analysis revealed that competence and leadership significantly impacted employee performance. These findings highlighted the critical role of competency development and leadership strengthening in enhancing employee performance. The binary logistic regression results indicated that 16 employees exhibited low performance, while 15 employees demonstrated high performance. Recommendations were made, including the need for the development of employee competencies, enhancement of leadership capabilities, monitoring of discipline and work initiatives, and periodic evaluation of qualifications. The implementation of these recommendations is expected to contribute to improved employee performance and service quality at BKPSDM Payakumbuh City.